2015
DOI: 10.5664/jcsm.5108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Sleep Disturbance and Recovery on Insulin-Like Growth Factor-1 (IGF-1): Possible Connections and Clinical Implications

Abstract: In their letter to the editor published in this issue of Journal of Clinical Sleep Medicine, Dong and Zhang 1 indicate a concern about our study that arises from their own related animal model study. Since the authors did not provide a citation for their associated research, we have limited insight into their perspective. Our study 2 included a cohort of military personnel with a high prevalence of traumatic brain injury (TBI), posttraumatic stress disorder (PTSD), and depression. There are signifi cant challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…As mentioned earlier, IGF-1 concentrations increased during SWS. Chennaoui et al 38 and Rusch et al 27 found that improved sleep quality led to increased IGF-1 concentrations. We found that IGF-1 levels at baseline (34.21 ± 8.20 ng/mL in the control group and 41.75 ± 11.09 ng/mL in the gabapentin group) were much lower than the normal range.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned earlier, IGF-1 concentrations increased during SWS. Chennaoui et al 38 and Rusch et al 27 found that improved sleep quality led to increased IGF-1 concentrations. We found that IGF-1 levels at baseline (34.21 ± 8.20 ng/mL in the control group and 41.75 ± 11.09 ng/mL in the gabapentin group) were much lower than the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Chennaoui et al 38 . and Rusch et al 27 . found that improved sleep quality led to increased IGF‐1 concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned earlier, IGF-1 concentrations increased during SWS. Chennaoui [44] and Rusch [45] found that improved sleep quality led to increased IGF-1 concentrations. We found that IGF-1 levels at baseline (34.21 ± 8.20 ng/mL in the control group and 41.75 ± 11.09 ng/mL in the gabapentin group) were much lower than the normal range.…”
Section: Discussionmentioning
confidence: 99%